Female-Released Sex Pheromones Mediating Courtship Behavior in Lysiphlebus testaceipes Males - Lo Pinto, Mirella (University of Wisconsin Library, 2013)
Ethological aspects and chemical communication at close-range between the sexes of Lysiphlebus testaceipes Cresson (Hymenoptera: Braconidae) have been investigated through behavioral bioassays and chemical analysis. The attractiveness toward males of whole-body extracts of females and males in hexane and acetone was evaluated, adopting male fanning behavior as a key behavioral component. Also, the activity of polar and nonpolar fraction of female-body extract in hexane obtained using solid-phase extraction technique was investigated. In order to identify cuticular compounds, male and female whole-body extracts with hexane and acetone were analyzed by gas chromatography-mass spectrometry. The results showed that males exhibit a behavior including 4 phases when exposed to virgin females: premount, mount, copulation, and post-copulation. A preliminary courtship of the male included wing fanning, an extension and vibration of the wings for 1 to 2 seconds. Also, some original aspects not described for other species were carried out. The average duration of the entire sequence of events was 138.80 ± 19.51 sec. Also, males displayed significantly more wing fanning behavior in response to female whole-body hexane extracts (70.83%) than female whole-body acetone extracts (33.3%). Furthermore, males did not respond to male-body extracts or to the control (pure hexane and acetone), suggesting that the sex pheromone is composed of cuticular hydrocarbons that are also involved in the male courtship behavior. When hexane extracts of whole females were fractionated on silica gel and exposed to males, more activity was recorded for the nonpolar fraction (50.0%) than the polar fraction (27.7%), but no significant statistical difference was found. Significant differences were detected comparing the control (not fractionated extract) with the polar fraction, but not with the nonpolar fraction. A homologous series of n-alkanes with chain lengths from C19 to C30 carbon atoms was identified and quantified in the solvent extracts of wasp males and females. Between male and female extracts, there was a statistically significant difference in the average quantity of some of these hydrocarbons, such as C(27), C(28), and C(29).